A quasi-linear Schrödinger equation with indefinite potential. Issue 4 (2nd April 2016) - Maia, L.A.; Oliveira Junior, J.C.; Ruviaro, R.
Abstract : In this paper, we investigate the existence of solution for the quasi-linear Schrödinger equation: in, where g has a subcritical growth and a kind of monotonicity and V is a potential, which changes sign. We employ the mountain pass theorem to obtain the existence of a non-trivial solution.